Destruction of Serbian National Identity and State in the Past Hundred Years - Bodin, Milenko (Sociološki pregled, 2025)
In my paper, I deal with the phenomenon of connection between deconstruction and destruction of national identity. Analyzing the relevant historical period, or the last hundred years, I point to the main elements of the Serbian national identity in attempts to dismantle it in relation to the fate of the state. I point to the internal factors of the defeatist discourse which, combined with external factors such as the supra-national project of Yugoslavia and the anti-national project of communist ideology, lead to the contemporary state of affairs of the residual character of the Serbian state and hybrid Serbian national identity. At the same time, this state of affairs, in which there is neither Yugoslavia nor communism, indicates the half-heartedness and incompleteness of the declared changes, i.e.., the “disguising” of the factors of the survival of anti-Serbian forms of identity both at the state level and at the national identity level. The need is articulated for formulating public policies aimed at improving the public discourse on the analyzed phenomena.